Soldier Zero. Volume one, One small step for man - Lee, Stan, 1922-2018 (Boom! Studios, 2011)
Having lost his legs during the Afghanistan War, Capt. Stewart Trautmann returned stateside with an understandingly negative attitude towards combat and violence, but his convictions are put to the test when a devastating meteor shower brings an alien parasite that transforms him into the ultimate weapon.